Finding freedom and rethinking power: Islamic piety in English high security prisons - Williams, Ryan J. (The British journal of criminology, 2018)
Prison ethnographers are often confronted with everyday examples of people trying to achieve some conception of the human good. Yet, descriptions of how people achieve this good in a prison environment—the techniques and aspirations of the ethical subject—are rare. With the help of recent developments in the anthropology of ethics and Foucault’s later work on freedom, this article examines the formation of ethical subjectivity practiced by some Muslim prisoners in two English high security prisons. The case of Muslim piety serves to deepen ethnographic research through recognizing the place of freedom and ethics in everyday life, and challenges criminological accounts of power and agency in view of how people accomplish virtue.